KAJIAN DOKUMEN INSTRUKSI KERJA DAN PENERAPANNYA DI LAPANGAN (STUDI KASUS PADA PROYEK PEMBANGUNAN JEMBATAN IRONAYAN) - , MOCH. AFAN ASADI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
completed within A project generally has the goal to be the right cost, right quality, on time and done safely. One attempt to reach the project goal is by doing each job with work instructions so that work can be done efficiently and effectively. The Regulation of the Minister of Public Works No. 04/PRT/M/2009 has required that the contractor has to make contract quality plan or called RMK (Rencana Mutu Kontrak). RMK is quality plan implementation and aims to be the quality assurance activities for the process and results of operations as required the work and the inside of RMK has work instructions. The purpose of this study is to evaluate the work instruction and give improvement for the work instruction document based on a case study of Ironayan bridge project located in Bantul, Daerah Istimewa Yogyakarta, by doing case study in there. This study is done by observation and then make work instructions based on theory in preparing work instructions, that is detailing the job with WBS, sorting the steps of worksusing network diagram and then write the narration of work instructions. Then this study comparing the work instruction in RMK and from the evaluation of this study. The result of this study found that the work instructions from RMK is not detailed enough. Some implementation in the field is not match with work instruction in RMK. The bridge structureâs work method (consist of fondation, abutment and girder work)have been documented in this study. This study also give a work instruction for several works in this bridge project. Based on the observation and WBS analysis that have been done, the work instructions for segmental precast prestress bridgeâs work can be presented in more detail.